Modulatory effects of mesenchymal stem cells on microglia in ischemic stroke - Hao, Lei; Yang, Yongtao; Xu, Xiaoli; Guo, Xiuming; Zhan, Qunling (Frontiers in Neurology, 2023)
Ischemic stroke accounts for 70%~80% of all stroke cases. Immunity plays an important role in the pathophysiology of ischemic stroke. Microglia are the first line of defense in the central nervous system. Microglial functions are largely dependent on their pro-inflammatory (M1-like) or anti-inflammatory (M2-like) phenotype. Modulating neuroinflammation via targeting microglia polarization toward anti-inflammatory phenotype might be novel therapeutic for ischemic stroke. Mesenchymal stem cells (MSC) and MSC derived extracellular vesicles (MSC-EVs) have been demonstrated to modulate microglia activation and phenotype polarization. In this review, we summarize physiological characteristics and functions of microglia in healthy brain, activation and polarization of microglia in stroke brain, the effects of MSC/MSC-EVs on the activation of MSC in vitro and in vivo and possible underlying mechanisms, providing evidence for a possible novel therapeutics for the treatment of ischemic stroke..